Optimisasi Suhu Pemanasan dan Kadar Air pada Produksi Pati Talas Kimpul Termodifikasi dengan Teknik Heat Moisture Treatment (HMT) - I Nengah Kencana Putra; Ni Wayan Wisaniyasa; Anak Agung Istri Sri Wiadnyani (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2016)
One of the physically starch modification technique is heat-moisture treatment (HMT). This technique can increase the resistance of starch to heat, mechanical treatment, and acid during processing. This research aimed to find out the influence of heating temperature and moisture content in the modification process of cocoyam starch with HMT techniques on the characteristic of product, and then to determine the optimum heating temperature and moisture content in the process. The research was designed with a complete randomized design (CRD) with two factors factorial experiment. The first factor was temperature of the heating consists of 3 levels namely 100 °C, 110 °C, and 120 °C. The second factor was the moisture content of starch which consists of 4 levels, namely 15 %, 20 %, 25 %, and 30 %. The results showed that the heating temperature and moisture content significantly affected water content, amylose content and swelling power of modified cocoyam starch product, but the treatment had no significant effect on the solubility of the product. HMT process was able to change the type of cocoyam starch from type B to type C. The optimum heating temperature and water content on modified cocoyam starch production process was 110 °C and 30 % respectively. Such treatment resulted in a modified cocoyam starch with moisture content of 6.50 %, 50,14 % amylose content, swelling power of 7.90, 0.0009% solubility, paste clarity of 96.310 % T, and was classified as a type C starch. ABSTRAKSalah satu teknik modifikasi pati secara fisik adalah teknik Heat Moisture Treatment (HMT). Teknik ini dapat meningkatkan ketahanan pati terhadap panas, perlakuan mekanik, dan asam selama pengolahan. Penelitian ini bertujuan untuk mengetahui pengaruh suhu dan kadar air pada proses modifikasi pati talas kimpul dengan teknik HMT terhadap karakteristik produk, dan selanjutnya menentukan suhu dan kadar air yang optimal dalam proses tersebut. Penelitian ini dirancang dengan rancangan acak lengkap (RAL) dengan percobaan faktorial dua faktor. Faktor pertama adalah suhu pemanasan, terdiri dari 3 taraf yaitu 100 °C, 110 °C, dan 120 °C. Faktor kedua adalah kadar air pati, terdiri dari 4 taraf yaitu 15 %, 20 %, 25 %, dan 30 %. Hasil penelitian menunjukkan, suhu pemanasan dan kadar air pati secara nyata mempengaruhi kadar air, kadar amilosa dan swelling power pati talas kimpul termodifikasi, tetapi tidak berpengaruh nyata terhadap kelarutannya. Proses HMT mampu mengubah tipe pati talas kimpul dari tipe B menjadi tipe C. Suhu pemanasan dan kadar air optimal pada produksi pati talas kimpul termodifikasi adalah 110 °C dan 30 %. Perlakuan tersebut menghasilkan pati talas kimpul termodifikasi dengan karakteristik seperti kadar air 6,50 %, kadar amilosa 50,14 %, swelling power 7,90, kelarutan 0,001 %, kejernihan pasta 96,31 % T, dan dengan klasifikasikan pati tipe C.